OP0038 Patients with Fibromyalgia (FM) do not Fulfill Classification Criteria for Axial Spondyloarthritis (AXSPA) but Patients with Axspa May Fulfill Classification Criteria for FM. (9th June 2015) - Baraliakos, X.; Regel, A.; Kiltz, U.; Kiefer, D.; Menne, H.-J.; Dybowski, F.; Igelmann, M.; Kalthoff, L.; Krause, D.; Saracbasi, E.; Schmitz-Bortz, E.; Braun, J.
Abstract : Background: Both patients with axial spondyloarthritis (axSpA) and patients with fibromyalgia (FM) are suffering from pain. The new ASAS classification criteria for axSpA have been recently challenged by arguing that FM patients could easily fulfill the clinical arm of the criteria, which could lead to overdiagnosis of axSpA and wrong treatment decisions. Objectives: To study similarities and differences between axSpA and FM using different sets of classification criteria and to assess the severity of wide-spread pain in both diseases. Methods: In this prospective study, patients were consecutively included if they were diagnosed with axSpA, or FM by a rheumatologist. Patients with rheumatoid arthritis (RA) were also included as an inflammatory control group. Patients on anti-TNF treatment were not included. Established classification and outcome parameters as well as standardized instruments were used in all patients. MRIs were performed in all axSpA and 20 FM patients. All axSpA and FM patients had radiographs. The Mann-Whitney-U test was used for statistical comparisons between groups. Results: A total of 214 patients was included: 93 with FM (7.5% HLA B27+), 91 with axSpA (79.1% HLA-B27+) and 30 with RA (53.3% seropositive). The mean age was 50.7±9.1, 43.0±12 and 58.4±11.9 years, respectively, and the mean symptom duration was comparable between groups: 6.6±6.9, 6.4±7.8 and 6.2±11.3, respectively. Expectedly, the gender ratio differed: FM and RA patients were mostly female (93.4% and 76.7%, respectively), as compared to axSpA patients (28.3%). The ASAS classification criteria were not fulfilled by any FM patient. In contrast, the 1990 and 2010 FM criteria were fulfilled by 98.3% and 100% of patients with FM, but also by 14.3% and 34.1% of axSpA (no differences between AS and nr-axSpA) and 30% and 46.7% of RA patients, respectively. The Fibromyalgia impact questionnaire (FIQ) values were 69.5±13.0, 45.4±19.3 (p<0.001) and 49.9±22.8, respectively, while the Health Assessment Questionnaire (HAQ) values were 1.7±0.5, 1.2±0.5 (p<0.001) and 1.6±0.8, for FM, axSpA and RA, respectively. FM patients reported the highest pain scores on a 0-10 numeric rating scale: 7.0±1.7 vs. 6.0±1.9 and 6.1±1.9 in axSpA and RA patients, respectively, while mean CRP values (mg/dl) were higher in axSpA (1.1±1.3) and RA (0.6±0.9) patients vs. FM (0.4±0.4) (both p<0.001). Conclusions: Importantly, no FM patients fulfilled ASAS classification criteria. Only a small proportion of patients with axSpA fulfilled any of the FM classification criteria. There was less overlap between patients with FM, axSpA and RA using the 1990 criteria as compared to the more sophisticated 2010 FM criteria. FM patients reported higher pain scores and more functional deficits. Some patients with widespread pain may have underlying axSpA - this differential diagnosis needs to be taken into account when dealing with the diagnosis of FM in daily practice. Disclosure of Interest: None declared